Regional assessment of choroidal vascularity index in patients with pre- and early-stage diabetic retinopathy using ultra-wide-field OCTA - Chen, Yulei; Xian, Haoxiong; Liu, Minghui; Dong, Xiuqing; Du, Shaolin (Frontiers in Medicine, 2024)
Purpose: To characterize the regional variations of choroidal vascularity index (CVI) in patients with diabetes mellitus (DM) using ultra-wide-field optical coherence tomography angiography (UWF-OCTA) and identify their correlations with the onset of diabetic retinopathy (DR). Methods: This cross-sectional, monocular-sampling study recruited 141 participants from four age-matched groups: no DM (NDM), no DR with early DM (EDM) and late DM (LDM), and mild-moderate non-proliferative diabetic retinopathy (mNPDR). UWF-OCTA was employed for circular scans centered on the fovea. CVI in the central region (0-1 mm) and 4 quadrants of the concentric rings with different ranges (1-3, 3-6, 6-9, 9-12, 12-15, 15-18 mm) was obtained for analysis together with their demographic and clinical data. The Area under the receiver operating characteristic curve (AUC) was calculated to assess the diagnostic efficacy for mNPDR and compared using the DeLong test. Results: The average CVI was lower in patients with mNPDR compared to other groups across all regions. Although there was no significant difference in DM duration between the LDM and mNPDR groups, a notable variance in CVI was observed, particularly (P = 0.0004) in the temporal quadrant of the 15-18 mm range (T18). CVI in T18 region was negatively correlated with creatinine levels, while positively correlated with body mass index and estimated glomerular filtration rate (Ps < 0.05). The CVI in the T18 region demonstrated superior diagnostic efficacy (AUC = 0.755), and when combined with those in other regions and clinical data, the AUC rose to 0.907, which was significantly better (P = 0.0280) than using clinical data alone. Conclusions: Reduced CVI was observed in the most peripheral region, highly predictive for mNPDR and associated with the declining renal function, thus enhancing the potential of UWF-OCTA to integrate into DM management and promote early DR screening.